2003
DOI: 10.1029/2002gl016719
|View full text |Cite
|
Sign up to set email alerts
|

The Dufek and Forrestal intrusions, Antarctica: A centre for Ferrar Large Igneous Province dike emplacement?

Abstract: Newly acquired aeromagnetic data indicate the presence of a dike swarm that may have acted as a magma transport and feeder system from the plume impact site up to 3,500 km to the Ferrar Large Igneous Province (FLIP). The Dufek and Forrestal intrusions, cover approximately 6,600 km2, and may form a ponding station between a mantle superplume responsible for Gondwana breakup and the FLIP sills and lavas along the Transantarctic Mountains into Tasmania and New Zealand. Prior to this survey, no feeder dike swarms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Subsequent evolution of the majority of magmas was by fractionation with a small amount of superimposed crustal contamination (Fleming et al 1995(Fleming et al , 1997. Although sourcing of the magmas from the Dufek Massif and transport through supracrustal sills has been proposed (Storey & Kyle 1997;Ferris et al 2003), it seems unlikely given the single unique composition of the capping lava flow(s), which are spread over 1600 km, the contrasting geochemical differences (e.g. MgO content) in the majority of the lavas from any one region compared with the next (central Transantarctic Mountains v. south Victoria Land v. north Victoria Land), and the presence of basement highs (Ross High, and between south Victoria Land and north Victoria Land; Elliot & Fleming 2008).…”
Section: Lower Jurassic Stratamentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent evolution of the majority of magmas was by fractionation with a small amount of superimposed crustal contamination (Fleming et al 1995(Fleming et al , 1997. Although sourcing of the magmas from the Dufek Massif and transport through supracrustal sills has been proposed (Storey & Kyle 1997;Ferris et al 2003), it seems unlikely given the single unique composition of the capping lava flow(s), which are spread over 1600 km, the contrasting geochemical differences (e.g. MgO content) in the majority of the lavas from any one region compared with the next (central Transantarctic Mountains v. south Victoria Land v. north Victoria Land), and the presence of basement highs (Ross High, and between south Victoria Land and north Victoria Land; Elliot & Fleming 2008).…”
Section: Lower Jurassic Stratamentioning
confidence: 99%
“…The magmas themselves were transported long distances at deep crustal levels or at the crust -mantle boundary prior to vertical migration into and through the upper crust and supracrustal rocks. Major dyke swarms for magma transport have not been recognized in outcrop, although they have been inferred from magnetic data near the Dufek Massif (Ferris et al 2003) and in the central Transantarctic Mountains (Goodge & Finn 2010). Bounding faults for this proposed rift system have not been identified, although the Hanson Formation arkoses and quartzose pebbly beds indicate that at least one fault could not have been too far distant; given the local thickness of Victoria Group strata, that fault could have had a cumulative displacement of as much as 2 km.…”
Section: Lower Jurassic Stratamentioning
confidence: 99%
“…Mapped and known Ferrar rocks form a long (3500 km) and narrow (160-320 km) belt in the Transantarctic Mountains that disappears beneath thick ice toward the pole and thinner ice over the West Antarctic rift basin. Geochemical evidence favors longdistance transport from areas in the Weddell Sea and/or Queen Maud Land via dikes or sills (Elliot et al, 1999;Ferris et al, 2003;Elliot and Fleming, 2008;Leat, 2008). However, the physical connection between Ferrar intrusions and those of Queen Maud Land remains enigmatic, and no large-scale feeders are known.…”
Section: Regional Feedersmentioning
confidence: 99%
“…Some hybrid models combine aspects of both passive and active models; the forces that drive plate motions place the continents under tension when subduction is taking place on both sides of the continent, but it is the arrival of a new plume that weakens them and causes them to split and form a new ocean (Hill 1991;Bott 1992;White 1992). With the initial breakup of Gondwana, many authors suggested that one or more centres of thermal activity responsible for the three Middle Jurassic igneous provinces (Karoo, Ferrar and Chon Aike) were situated in the Weddell Sea sector between South America, southern Africa and Antarctica (Storey & Kyle 1997;Elliott & Fleming 2000;Ferris et al 2000Ferris et al , 2003Storey et al 2001). The thermal anomalies may have been responsible for Gondwana breakup by doming of the lithosphere and gravitational collapse, leading to continental rifting (active rifting model; Storey & Kyle 1997).…”
Section: Thermal Anomaly/mantle Plume/hotspotmentioning
confidence: 99%